Good governance of zakat: Constitutional legitimacy of BAZNAS from the perspective of islamic economics - Bobby Ferly; Ade Mulazid; Supriyono; Athia Kamilah; Bahrul Yaman; Cut Erika (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing significance of Islamic social finance has intensified scholarly attention toward zakat institutions as strategic instruments for socio-economic development, particularly in relation to governance quality and institutional legitimacy. This study aims to systematically examine the relationship between constitutional legitimacy and good governance within the context of zakat management, with a specific focus on the National Board of Zakat (BAZNAS) from an Islamic economics perspective. Employing a qualitative design through a Systematic Literature Review (SLR), this study follows the PRISMA framework to identify, screen, and analyze 50 peer-reviewed articles indexed in Scopus published between 2015 and 2025. Data were analyzed using thematic analysis supported by structured coding to identify patterns in governance dimensions, legitimacy constructs, and theoretical frameworks. The findings reveal that good governance, characterized by transparency, accountability, and effectiveness, serves as the central determinant of institutional credibility and zakat compliance. While constitutional legitimacy provides a formal legal foundation, it does not automatically ensure public trust; instead, legitimacy is dynamically constructed through governance performance. The study further highlights the mediating role of trust in linking governance practices to compliance behavior, as well as the emerging significance of digital transformation and SDG alignment in strengthening institutional impact. Theoretically, this study integrates Institutional Theory with Maqasid al-Shariah to propose a more comprehensive framework for zakat governance. In conclusion, the effectiveness and sustainability of zakat institutions depend on the continuous alignment between legal authority, governance quality, and ethical principles, positioning zakat as both a religious obligation and a strategic tool for sustainable socio-economic development.